Problem-oriented project -based learning (POPBL): an initiative to encourage soft skills expansion among students at a public university - Fatmawati, Latada; Hafizoah, Kassim (Journal of Global Business and Social Entrepreneurship (GBSE), 2017)
This paper discusses the implementation of Problem -Oriented Project -Based Learning (POPBL) at a technical-based university in the East Coast of Malaysia. The POPBL was employed to incorporate the theoretical knowledge and application of soft skills among students. This paper meant to report (i) challenges encountered by students in the process of POPBL’s implementation and (ii) students’ attitude in managing hindrances to complete the task. Observation was made during Soft Skills course offered to 3rd year undergrads. The groups encompass of various faculties were formed into small group of 6-7 members. Every 15 smalls groups were supervised by a lecturer. Along the 14-week course, students were required to do; (i) a survey and identify a problem based on designated theme, (ii) designed a project proposal complete with an action plan to solve the identified problem and, (iii) prepare a complete report furnished with related documents and images. Assessment on technical aspect was based on project proposal and final report, while Soft Skills applications were observe through work process i.e., work progress (Leadership Skills), task distribution and coordination (Team Working), flow of communications (Communication Skills) time management (Ethics and Moral Professional) and quality of solution (Critical Thinking and Problem Solving). The findings advocate that on the technical aspect, students were moderately able to prepare a project report but they need lots of assistance in preparing project proposal particularly in analyzing and identifying a problem. On Soft Skills application aspect, most students reported an adequate skills expansion particularly their team working and communication. The higher and low performers were captured via four progress meetings series conducted by the lecturers in charge. However, it was difficult to ascertain the level of performance for the average students due to disability of peer assessors to capture actual performance due to pity.